I'm a Giant: Walking in Large Virtual Environments at High Speed Gains - Abtahi, Parastoo; Gonzalez Franco, Mar; Ofek, Eyal; Steed, Anthony (CHI Conference on Human Factors in Computing Systems Proceedings (CHI 2019), 2019)
Advances in tracking technology and wireless headsets enable walking as a means of locomotion in Virtual Reality. When exploring virtual environments larger than room-scale, it is often desirable to increase users' perceived walking speed, for which we investigate three methods. (1) Ground-Level Scaling increases users' avatar size, allowing them to walk farther. (2) Eye-Level Scaling enables users to walk through a World in Miniature, while maintaining a street-level view. (3) Seven-League Boots amplifies users' movements along their walking path. We conduct a study comparing these methods and find that users feel most embodied using Ground-Level Scaling and consequently increase their stride length. Using Seven-League Boots, unlike the other two methods, diminishes positional accuracy at high gains, and users modify their walking behavior to compensate for the lack of control. We conclude with a discussion on each technique's strength and weaknesses and the types of situation they might be appropriate for.